Effects of exposure to bodies of different sizes on perception of and satisfaction with own body size: two randomized studies. Issue 5 (9th May 2018) - Bould, Helen; Carnegie, Rebecca; Allward, Heather; Bacon, Emily; Lambe, Emily; Sapseid, Megan; Button, Katherine S.; Lewis, Glyn; Skinner, Andy; Broome, Matthew R.; Park, Rebecca; Harmer, Catherine J.; et al.
Abstract : Body dissatisfaction is prevalent among women and associated with subsequent obesity and eating disorders. Exposure to images of bodies of different sizes has been suggested to change the perception of 'normal' body size in others. We tested whether exposure to different-sized (otherwise identical) bodies changes perception of own and others' body size, satisfaction with body size and amount of chocolate consumed. In Study 1, 90 18–25-year-old women with normal BMI were randomized into one of three groups to complete a 15 min two-back task using photographs of women either of 'normal weight' (Body Mass Index (BMI) 22–23 kg m −2 ), or altered to appear either under- or over-weight. Study 2 was identical except the 96 participants had high baseline body dissatisfaction and were followed up after 24 h. We also conducted a mega-analysis combining both studies. Participants rated size of others' bodies, own size, and satisfaction with size pre- and post-task. Post-task ratings were compared between groups, adjusting for pre-task ratings. Participants exposed to over- or normal-weight images subsequently perceived others' bodies as smaller, in comparison to those shown underweight bodies ( p < 0.001). They also perceived their own bodies as smaller (Study 1, p = 0.073; Study 2, p = 0.018; mega-analysis, p = 0.001), and felt more satisfied with their size (Study 1, p = 0.046; Study 2, p = 0.004; mega-analysis, p = 0.006). There were no differences in chocolate consumption. This study suggests that a move towards using images of women with a BMI in the healthy range in the media may help to reduce body dissatisfaction, and the associated risk of eating disorders.